MR image reconstruction with autoregressive moving average - Salami, Momoh Jimoh Emiyoka; Najeeb, Athaur Rahman; Khalifa, Othman Omran; Ariffin, Kamarul Ariffin (Faculty of Engineering International Islamic University Malaysia, 2007)
MRI Image rconstruction from 2D ARMA is proposed in this paper. Conventionally MRI images are reconstructed using 2D DFT in all type of MRI data acquisition techniques due to its computational effectiveness and simplicity. However the use of DFT leads to artifacts and appearance of Gibbs Ringing. Various types of windows are used to overcome this issue, however the inherit issues of DFT still surfaces. Modified TERA method is proposed as a solution for 2D ARMA in this paper. For simulations, images in form of raw data are downloaded from Philips(t) MRI Machines. Later 2D DFT and M-TERA method is used to reconstruct and results shows that m-TERA ourperform the 2D DFT in various ways.